The Impact of Project Management Practices on Institutional Excellence: An Applied Study of the Tarahum Committee for the Care of Prisoners in Riyadh - Alharbi, Seham Hamdan Dasan Almakhlafi (Journal of Economic, Administrative and Legal Sciences, 2025)
The current study aimed to reveal and identify the impact of project management practices on institutional excellence in the Tarahum Committee. The committee faces several challenges, most notably the inefficiency in resource management, the absence of effective monitoring and evaluation mechanisms, and cultural and organizational challenges that hinder the achievement of its goals. In addition, the committee faces difficulty in adapting to the continuous changes in the work environment. The study relied on the descriptive analytical approach, and relied on the questionnaire as a tool for collecting data from members of the Tarahum Committee. The questionnaire was designed based on the main problems facing the committee. The study was conducted on a sample of (8) employees and managers of the General Secretariat of the Tarahum Committee for Prisoners’ Care in Riyadh. The results of the study concluded that project management practices have a positive impact on institutional excellence. The average evaluation of resource management was (3.5) out of (5). The study results also showed that (65%) of the participants indicated that resource management was improved using best practices, as the average effective use of resources was (3.38) out of (5), and the overall satisfaction of users was (3) out of (5). The study results also indicated that the committee’s flexibility in dealing with challenges was (3.25) out of (5). The study recommended the need to improve planning and resource allocation, enhance monitoring and evaluation mechanisms, develop strategies to address cultural and organizational challenges, and develop flexible strategies to adapt to continuous changes in the work environment to enhance innovation and ensure the sustainability of institutional excellence.